A Comparative Approach to Market Wide Herding - Zwane, Sibongile (University of the Witwatersrand, Johannesburg, 2024)
This thesis prices, investigates and models market wide herding for selected emerged economies (i.e., U.S. and UK) and named emerging markets (i.e., Taiwan and South Africa) for bonds, equities and real estate sectors. To investigate the mentioned theme/topic, this study develops three hypotheses: (i) the selected indices are prone to market wide herding, (ii) there are systematic volatility patterns during herding process, and finally, (iii) there is positive herding in the real estate sector. The findings are as follows. First, there are persistent herding behaviour of the used indices and moreover, herding behaviour is both within and in between indices. The latter statement is consistent with the findings of Kola (2021). Second, herding exists in volatility towards to the developed economies from emerging markets, irrespective of the product type. Finally, there is definitive herding in the real estate industry, in particular, in indices and not so much in stand-alone REITs. Interestingly, evidence of herding is model sensitive. Finally, the implications are as follows. First, when you invest in bonds, equities and real estate indices, investors should mitigate against herding effects. Second, integration of products, in the context of bonds, equities and real estate, should be encouraged as that increases the levels of information symmetry. The latter statement implies that investing in financial markets would be risky (See; Kola 2021 and Sibongile 2021). Third and finally, intraday investors should have deep insights about emerging markets as emerging financial markets herd towards to emerged markets.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy i, In the Faculty of Engineering and the Built Environment , School of Construction Economics and Management, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; bonds; CSAD; CSSD; equities; herding; LSV; real estate; volatility JEL: G12; G13; G15; SDG-8: Decent work and economic growth